Nuclear energy and the environment - Chien, M Wai (American Chemical Society, 2013)
This book presents key issues which must be addressed in order to develop sustainable nuclear energy technologies for the 21st century, such as responsible management of nuclear wastes, more efficient processes for conversion of uranium to energy, and effective and secure techniques for recycling used nuclear fuel.